2006
DOI: 10.1007/s00109-005-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of G-CSF on left ventricular remodeling and heart failure after acute myocardial infarction

Abstract: Granulocyte colony-stimulating factor (G-CSF) is a hematopoietic cytokine that promotes proliferation and differentiation of neutrophil progenitors. G-CSF also possesses immunomodulatory properties. G-CSF-induced hematopoietic stem cell mobilization is widely used clinically for transplantation. After it was recently reported that G-CSF mobilizes bone marrow stem cells (BMSCs) into the infarcted hearts and accelerates the differentiation into vascular cells and cardiac myocytes, myocardial regeneration utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…G-CSF-induced hematopoietic stem cell mobilization has been widely used for transplantation. Many studies have reported that G-CSF mobilizes BM stem cells into infarcted cardiac tissue and accelerates their differentiation into vascular cells and cardiac myocytes [18]. The role of G-CSF has also been investigated in such inflammatory bowel diseases as Crohn's disease and ulcerative colitis [19].…”
Section: Introductionmentioning
confidence: 98%
“…G-CSF-induced hematopoietic stem cell mobilization has been widely used for transplantation. Many studies have reported that G-CSF mobilizes BM stem cells into infarcted cardiac tissue and accelerates their differentiation into vascular cells and cardiac myocytes [18]. The role of G-CSF has also been investigated in such inflammatory bowel diseases as Crohn's disease and ulcerative colitis [19].…”
Section: Introductionmentioning
confidence: 98%
“…G-CSF exerts reparative and regenerative effects in various ischemic tissues, including heart [3,5], brain [6] and kidney [7]. Additionally, pretreatment with G-CSF attenuates renal ischemia/ reperfusion injury, and this cytoprotection seems to be associated with its anti-apoptotic action [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, recombinant human CSF3 mobilized bone marrow stem cells to damaged brain tissue, induced the release of a neurotrophic factor and reduced brain tissue damage [43,44]. In addition, CSF3 mobilized bone marrow stem cells to myocardial infarction sites and promoted cardiac myocyte repair [35,45]. …”
Section: Discussionmentioning
confidence: 99%